Marine diet and tobacco exposure affects mercury concentrations in pregnant women (I) from Baja California Sur, Mexico - Ramón Gaxiola-Robles; Rebecca Bentzen; Tania Zenteno-Savín; Vanessa Labrada-Martagón; J. Margaret Castellini; Alfredo Celis; Todd O’Hara; Lía Celina Méndez-Rodríguez (Toxicology Reports, 2014)
Seafood provides essential polyunsaturated fatty acids (PUFA) and other nutrients to pregnant women and their fetus(es) while a diet rich in finfish can be a major pathway of monomethyl mercury (MeHg+) exposure. We measured total mercury concentration ([THg]) in hair samples provided by 75 women in Baja California Sur (BCS) to assess its relationship with age, parity, tobacco smoke exposure, and diet based on survey methodologies. Generalized linear models (GLM) were used to explain the possible association of the different variables with [THg] in hair. Median [THg] in hair was 1.52 μg g−1, ranging from 0.12 to 24.19 μg g−1 and varied significantly by segment. Approximately 72% (54/75) of those evaluated exceed 1 μg g−1 [THg] and 8% (6/75) exceed 5 μg g−1 [THg] in hair. Although frequency of fish consumption contributed significantly to explaining hair [THg], fish consumption only explained 43% of [THg] in a GLM incorporating tobacco exposure and body mass index. This study establishes possible relationships among multiple potential sources of exposure and other factors related to [THg] in hair of women in the prenatal period. A more detailed examination of other sources of exposure and factors contributing to [THg] is warranted.